Warfare [videorecording (Blu-Ray)] - Garland, Alex, 1970-; Mendoza, Ray; Woon-A-Tai, D'Pharaoh McKay, 2001-; Poulter, Will; Jarvis, Cosmo, 1989-; Connor, Kit, 2004-; Bennett, Finn, 1999-; Smith, Taylor John, 1995-; Gandolfini, Michael, 1999-; Bradley, Adain; Centineo, Noah, 1996-; Holtzman, Evan; et al. (A24, 2025)
"Warfare embeds audiences with a platoon of American Navy SEALs in an Iraqi apartment building as they surveil a group of insurgents plotting an attack. A visceral, boots-on-the-ground story of modern warfare, told like never before: in real time and based on the memory of the people who lived it"--